2017
DOI: 10.3892/or.2017.5706
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of BAG3 promotes the sensitivity of ovarian cancer cells to cisplatin via inhibition of autophagy

Abstract: Abstract. Ovarian cancer is the most lethal disease among all gynecological malignancies. Interval cytoreductive surgery and cisplatin-based chemotherapy are the recommended therapeutic strategies. However, acquired resistance to cisplatin remains a big challenge for the overall survival and prognosis in ovarian cancer. Complicated molecular mechanisms are involved in the process. At present, increasing evidence indicates that autophagy plays an important role in the prosurvival and resistance against chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…The present study identified that BAG3 was highly expressed in CC tissues and cell lines. Consistently, previous reports also demonstrated that BAG3 was over-expressed in colorectal and prostate cancer [ 10 13 ]. These findings indicate that BAG3 acts as an oncogene, which was responsible for the progression of cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study identified that BAG3 was highly expressed in CC tissues and cell lines. Consistently, previous reports also demonstrated that BAG3 was over-expressed in colorectal and prostate cancer [ 10 13 ]. These findings indicate that BAG3 acts as an oncogene, which was responsible for the progression of cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…BAG3, a member of six BAG families, contains a conserved domain, and interacts with Hsp-70 [ 6 9 ]. It has been reported that BAG3 is highly expressed in many kinds of primary tumors, including ovarian cancer, and glioblastoma [ 10 13 ]. In addition, BAG3 is able to modulate some tumor biology processes, involving cell apoptosis, growth, cytoskeleton organization, and differentiation [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, resistance to various types of therapy is characterized by enhanced basal levels of autophagy, as defined by increased conversion of LC3‐I to LC3‐II, increased numbers of LC3B puncta per cell, upregulated numbers of autophagolysosomes, and degradation of p62 . For example, cisplatin‐resistant clones of ovarian cancer cell lines as well as an oral squamous cell carcinoma cell line were characterized by enhanced levels of autophagic flux . In radiotherapy‐resistant breast cancer cells, ionizing radiation also elevated basal autophagy levels, indicating a protective effect of autophagy against treatment .…”
Section: Part I: the Role Of Autophagy In Cancer Cellsmentioning
confidence: 99%
“…For pancreatic cancer, it has been shown that primary tumors and cell lines exhibit increased autophagy, while autophagy inhibition (genetic and pharmacological) results in increased reactive oxygen species (ROS) formation and DNA damage, while treatment of tumor-bearing mice with the autophagic flux-inhibitor chloroquine (CQ) improved overall survival [40]. In another study Qiu et al showed that autophagy induced by cisplatin protected ovarian cancer cells [41], while DeVorkin et al could, in fact, show that cancer cells of clear-cell ovarian cancer depend on autophagy for their survival [42]. From a mechanistic perspective, it should, however, be noted that CQ is not a highly selective inhibitor of autophagy.…”
Section: Pro-survival Autophagymentioning
confidence: 99%